Mitral Annular Calcification is Associated with Severe Coronary Artery Disease in Patients Under 65 Years Old - Rahman, Mohammad Arifur; Majumder, AAS; Chowdhury, NA; Rahman, MZ; Islam, AKMM; Ullah, M; Razzaque, MA; Romel, SMA (Cardiovascular Journal, 2013)
Background: Mitral annular calcification (MAC) is degenerative, fibrous calcification of the mitral valve annulus. It is more common in people over 70 years old. It is a marker of increased cardiovascular risk which occurs in a graded fashion by MAC severity. The aim of this study was to evaluate the association of Mitral annular calcification with severity of coronary artery disease (CAD) in patients under 65 years old. Methods: A total of 140 patients with IHD were enrolled by purposive sampling. Study populations were divided into MAC group and non MAC group. MAC was detected by Trans-thoracic echocardiography as an intense echo-producing structure located at the junction of the atrio-ventricular groove and posterior mitral leaflet in parasternal long axis view. MAC is measured in millimeters from the leading anterior to the trailing posterior edge and quantified as mild to moderate (1 to 4 mm) and severe (>4 mm) considering its thickness. Assessment of angiographic severity of CAD was done in the same hospital stay by Vessel score, Friesinger score and Leaman score. Results: Patients of MAC and non MAC groups were similar in terms of age and sex. Smoking (p=0.001) and family history of IHD (p=0.03) were significantly higher in MAC group. Anterior MI was significantly higher in MAC group (p=0.03). Left main and TVD were significantly higher in MAC group (p=0.001, p=0.01) whereas normal vessels were more in non MAC group (p=0.001). Intermediate and high Friesinger score (e5) were significantly higher in MAC group whereas low Friesinger score (<5) were more in non MAC group. There was significant (p=0.01) positive correlation between MAC and CAD severity in terms of vessel score (r=0.76) Friesinger score (r=0.75) and Leaman score(r=0.42). Multivariate logistic regression analysis showed that MAC was independent predictors of significant CAD (p=0.02, OR= 2.84). Conclusion: Echocardiographically detected mitral annual calcification (MAC) can be an independent predictor of significant coronary artery disease. There is positive correlation between severity of MAC and severity of CAD. Cheap, available and radiation free nature of the echocardiographic detection of MAC may be a marker of significant CAD. Cardiovascular Journal Volume 6, No. 1, 2013, Page 10-16 DOI: http://dx.doi.org/10.3329/cardio.v6i1.16109